Large deflection analysis of moderately thick composite plates - Tanrıöver, Hakan; Şenocak, Erol (Computer Assisted Methods in Engineering and Science; Vol 13 No 4 (2006), 2022)
Large deflection analysis of laminated composite plates is considered. The Galerkin method along with Newton-Raphson method is applied to large deflection analysis of laminated composite plates with various edge conditions. First order shear deformation theory and von Kármán type nonlinearity are utilized and the governing differential equations are solved by choosing suitable polynomials as trial functions to approximate the plate displacement functions. The solutions are compared to that of Chebyshev polynomials and finite elements. A very close agreement has been observed with these approximating methods. In the solution process, analytical computation has been done wherever it is possible, and analytical-numerical type approach has been made for all problems.